Evaluation of pollination of date palm trees of the Halawi variety with pollen of the Canary and green Ghanamy date palms on productivity and chemical components of fruits - Ati, Muntaha AbdulZahra; Abdullah, AbdulSamad Abood (Journal of agricultural, environmental and veterinary sciences, 2025)
This study, which was conducted in a private orchard in the Abu Al-Khaseeb area of Basrah Governorate during the 2022 growing season, aimed to test the effectiveness of Canary palm pollen as a new pollinator for Halawi date palm trees, and to compare its results with the most commonly used traditional pollinator, the green Ghanami palm, in terms of the productive and chemical characteristics of the fruits. A group of Halawi date palm trees were selected to be pollinated with the green Ghanami palm and Canary palm pollen. To ensure the success of the pollination process and prevent any mixing between the pollen and to avoid the occurrence of the Metaxenia phenomenon, the pollinated shoots were covered with paper bags for two weeks. After this period, the bags were removed and fruit samples were taken at the Khalal, Rutab and Tamer stages to measure the productive, physical and chemical characteristics of the fruits. The pollinated shoots were tightly covered with paper bags to ensure pollination, avoid mixing during pollination, and avoid Metaxenia . They were left for two weeks to ensure fruit set. The bags were then removed and fruit samples were taken at the Khalal, Rutab, and Tamr stages to measure some physical, chemical, and productive characteristics of the fruits. The results showed that pollination with the pollen of the green Ghannami palm led to an increase in both the weight and length of the fruit at the Khalal stage. It also contributed to raising the content of total soluble proteins and total soluble phenols at the Rutab stage to reach 204.3 and 0.185 mg.100 g-1, respectively, compared to the Canary pollen. On the other hand, pollination with the pollen of the Canary palm led to a decrease in the content of total soluble phenols at the Rutab stage to reach 0.044 mg.100 g-1, compared to the green Ghannami pollen, which amounted to 0.185 mg.100 g-1, and raised the content of total soluble carbohydrates and free amino acids at the Rutab stage. To reach 24.5 mg.g-1 and 28.6 mg.g-100 g-1, respectively. No significant differences were recorded between the two pollination in terms of total soluble solids.